Left double-lumen tube with or without a carinal hook: A randomised controlled trial. Issue 6 (June 2015) - Dumans-Nizard, Virginie; Parquin, Jean-François; Moyer, Jean-Denis; Dreyfus, Jean François; Fischler, Marc; Le Guen, Morgan
Abstract : BACKGROUND: Left double-lumen tracheal tubes (DLTs), with or without a hook to engage the carina, remain the standard device for lung isolation during anaesthesia. OBJECTIVE: The purpose of the study was to compare these DLTs with and without a hook. DESIGN: A randomised, controlled, single-blinded study. SETTING: University hospital. PARTICIPANTS: One hundred and eighty-four patients undergoing lung resection. MAIN OUTCOME MEASURE: Time required to position the tube from the introduction of the tube into the mouth to confirmation of correct placement in the supine position. RESULTS: Baseline characteristics were well balanced between the groups. Time to place DLTs was similar in both groups: median (interquartile range, IQR) 81.0 (50.0 to 146.2) s for DLTs without a hook and 67.5 s (45.0 to 138.7) for DLTs with a hook ( P = 0.43). The incidence of adequate position at the first attempt was 68.5% in the No hook group and 69.6% in the Hook group ( P = 0.95). Patients in both groups suffered similar incidences of sore throat at day 0 and day 1 ( P = 0.80 and P = 0.20, respectively). No major lesion of the vocal cords or tracheobronchial tree was discovered and the incidence of minor lesions was similar in both groups. CONCLUSION: When a DLT is used, the presence of a carinal hook gives neither advantage nor added complications. TRIAL REGISTRATION: ClinicalTrials.gov, NCT00969683.